2006
DOI: 10.1111/j.1442-2050.2006.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide imaging for the assessment of esophageal motility disorders in mixed connective tissue disease patients: relation to pulmonary impairment

Abstract: Esophageal functional abnormalities may lead to regurgitation, chronic esophagitis and life-threatening conditions such as aspiration pneumonia. In mixed connective tissue disease patients, previous reports showed that esophageal dysfunction varies according to the method employed for investigation. Our study was conceived to: (i) assess esophageal motility and mucosal aspects in patients with mixed connective tissue disease by endoscopy, cine-esophogram and scintigraphy focusing on the prevalence of each exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
(35 reference statements)
1
8
0
Order By: Relevance
“…Pulmonary dysfunction and oesophageal hypomotility are recognised manifestations of MCTD and may often be detected prior to the onset of symptoms. In the studies presented, a significant correlation was demonstrated between severe oesophageal motor dysfunction (on manometry or radionuclide imaging study) and the presence of ILD (as assessed by PFT, DLCO and HRCT) [Evidence B] 24, 25 . These findings suggest that ILD may be associated with regurgitation of food in patients with MCTD because it is more common in those with oesophageal dilatation on CT and with severe oesophageal dysfunction on manometry.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Pulmonary dysfunction and oesophageal hypomotility are recognised manifestations of MCTD and may often be detected prior to the onset of symptoms. In the studies presented, a significant correlation was demonstrated between severe oesophageal motor dysfunction (on manometry or radionuclide imaging study) and the presence of ILD (as assessed by PFT, DLCO and HRCT) [Evidence B] 24, 25 . These findings suggest that ILD may be associated with regurgitation of food in patients with MCTD because it is more common in those with oesophageal dilatation on CT and with severe oesophageal dysfunction on manometry.…”
Section: Discussionmentioning
confidence: 88%
“…The relationship between gastro‐oesophageal reflux and interstitial lung disease in patients with MCTD was evaluated in two studies (Table 3) [Evidence B] 24, 25 . In one prospective small‐sample study, the presence of ILD was assessed by PFT and HRCT, while oesophageal abnormalities were assessed by manometry, 24‐h oesophageal pH monitoring and the presence of oesophageal dilation on CT scan 24 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, videofluoroscopy (Palmer and others 1993; Buettner and others 2002; Saitoh and others 2007), ultrasonography (Furukawa and others 2003; de Wijk and others 2006), radionuclide imaging (Caleiro and others 2006; Bogaardt and others 2007), and fiberoptic endoscopy (Leder 1998; Leder and others 2005) have been typically used for monitoring swallowing. These assessments, however, have certain limitations in food science applications due to their high cost and need for medical training (Kohyama and others 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The ETT assessment is used to complete the diagnosis of diseases, such as gastroesophageal reflux [12][13][14] , dysphagia [15,16] , esophagitis [17,18] , and achalasia [6,19,20] . The latter studies are commonly performed with scintigraphic and manometric techniques [21] , in healthy [22] , geriatric [23] , and pediatric patients [24] , despite the use of ionizing radiation and catheters in each test, respectively. Recently, several assessments were performed using the biomagnetic technique, including gastric emptying time [25] and colon transit time [26] .…”
Section: Introductionmentioning
confidence: 99%